Holey tungsten oxynitride nanowires novel anodes efficiently integrate microbial chemical energy conversion and electrochemical energy storage - Yu, Minghao (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.